SPATIAL AND TEMPORAL DISTRIBUTION OF FISH IN THE FLOODPLAIN OF KUMBE RIVER. PAPUA - Yoga Candra Ditya; Arif Wibowo; Husnah Husnah (Research Center for Fisheries, 2018)
Expansion of land clearance mostly for plantation is the big issue in Indonesia including in Papua. Its effect is not only to the catchment area but it also affects fisheries resources. The stress effect occurs worsen in Kumbe River and its floodplain area by the present of introduced fish species such as snakehead (Channa striata) and nile tilapia (Oreochromis niloticus). Spatial and temporal fish distributions are important information for the sustainable fisheries resource and theirs utilization. Study on spatial and temporal fish distribution covering four types of swamp ecosystem of Kumbe River was conducted during April-September 2014 and Mei-November 2015. Explorative field survey was conducted in four different ecosystem types in Kumbe River floodplain areas. Ecological data was collected from four sampling sites in each ecosystem type during high water precipitation (April and May) and low water precipitation (August. September and November). and fish samples were collected with different mesh sizes of gillnet fishing experiment conducted in four sampling sites. Parameters measured were fish important relative index and physical and chemical water quality parameters. The results noted 18 fish species deriving from 13 families. The Arridae with its blue catfish (Neoarius graeffei) dominated almost 90% of fish catch both spatial and temporal. Hydrological dynamic seems the key of trigger factor for the spatial and temporal distribution of fish and dynamic of habitat and water quality characteristic in the floodplain of Kumbe River.